Amasya İlahiyat dergisi = Amasya theology journal (Amasya University, 2013)
"Amasya Theology Journal is a peer-reviewed Journal published twice a year as July and December by the University of Amasya. (June 30 – December 30). It aims to publish articles, book reviews and symposium reviews on theology and social sciences and to share these studies with public"